CYBERCRIME AND DAMAGES IN CIVIL LAW: TECHNICAL MEASURES AND CASE LAW IN DISPUTE RESOLUTION - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2026)
This article analyses the relationship between cybercrime and claims for damages under Indonesian civil law, focusing on technical approaches and case law in dispute resolution. The research method is a legal-normative literature review examining legislation, court rulings, academic literature and policy documents relating to cybercrime, electronic evidence, restitution and Article 1365 of the Civil Code. The findings reveal three main conclusions. Firstly, the incidence of cybercrime has increased significantly, resulting in complex material and immaterial losses. Secondly, technical measures such as digital forensics, digital asset tracing, the authentication of electronic evidence, and the role of forensic experts are prerequisites for proving claims and recovering losses. Thirdly, case law and judicial practice have opened up avenues for restitution and civil claims, but these still face obstacles in the form of imprecisely formulated claims, challenges in authenticating evidence, and inconsistencies in the assessment of non-material damages. The article recommends harmonising legal standards between the criminal and civil spheres, strengthening digital forensic capabilities within law enforcement agencies, and developing jurisprudential guidelines to enhance the certainty and effectiveness of restoring victims’ rights.